Brexit’s Impacts on The Arabian Gulf - YENIGUN, CUNEYT; AL-MAMARI, SULTAN ZAYID SALIM (The journal of contemporary issues in business and government, 2021)
This study aims to highlight the most prominent effects of Brexit on the Britain-GCC countries’ relationship, by investigating the developments that occurred in the security and economic aspects after the referendum’s outcome in 2016 and drawing the future of this relationship. In addition, it is important to track the evidence that indicates Britain's return to the region as one of the important alternatives to compensate for its expected losses after Brexit. This study examines that Britain would play an important role in the economy and security of the GCC countries and in return, the GCC countries will help Britain to reduce the expected economic losses following the Brexit by using their sovereign funds to invest in the United Kingdom. It can be inferred that the future relationship between the two parties should be a “win, win” technique by activating their partnership and reducing barriers in order to reach free trade agreements.